2014
DOI: 10.1021/bm401800y
|View full text |Cite
|
Sign up to set email alerts
|

Direct Solvation of Glycoproteins by Salts in Spider Silk Glues Enhances Adhesion and Helps To Explain the Evolution of Modern Spider Orb Webs

Abstract: The evolutionary origin of modern viscid silk orb webs from ancient cribellate silk ancestors is associated with a 95% increase in diversity of orb-weaving spiders, and their dominance as predators of flying insects, yet the transition's mechanistic basis is an evolutionary puzzle. Ancient cribellate silk is a dry adhesive that functions through van der Waals interactions. Viscid threads adhere more effectively than cribellate threads because of the high extensibility of their axial silk fibers, recruitment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
110
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(118 citation statements)
references
References 41 publications
8
110
0
Order By: Relevance
“…Spiral thread stickiness, however, was not significantly affected by feeding treatment so the second possibility seems the most likely. A greater concentration of HPO 4 but lower concentration of KNO 3 in the spiral glues of the webs of spiders fed adult crickets is somewhat difficult to explain, primarily because so little is known about the costs, benefits and functional significance of these salts within orb web gluey silks (Sahni et al, 2014a). A tentative explanation is that because nitrates are needed for other body functions (Frost et al, 2005) KNO 3 becomes more sparingly used as more spiral threads, and consequently more gluey silk, are deposited (Opell et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spiral thread stickiness, however, was not significantly affected by feeding treatment so the second possibility seems the most likely. A greater concentration of HPO 4 but lower concentration of KNO 3 in the spiral glues of the webs of spiders fed adult crickets is somewhat difficult to explain, primarily because so little is known about the costs, benefits and functional significance of these salts within orb web gluey silks (Sahni et al, 2014a). A tentative explanation is that because nitrates are needed for other body functions (Frost et al, 2005) KNO 3 becomes more sparingly used as more spiral threads, and consequently more gluey silk, are deposited (Opell et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The salts induce cohesive forces that cause the aggregate silk to coalesce along the flagelliform thread into droplets that resemble beads on a string (Sahni et al, 2014b;Opell et al, 2015). The salts also facilitate water uptake from the environment into the droplets (Vollrath et al, 1990;Sahni et al, 2010Sahni et al, , 2011Townley and Tillinghast, 2013), which keeps the droplets hydrated, and thus solvates the glycoproteins (Sahni et al, 2011(Sahni et al, , 2014a.…”
Section: Introductionmentioning
confidence: 99%
“…Over the course of a day, the volumes of these hygroscopic droplets change as they respond to changes in environmental humidity (Townley et al, 1991;Opell et al, 2013). Although the allocation of absorbed atmospheric water has not been fully studied, some of it solvates the glycoprotein, ensuring its interaction with a surface, some of it hydrates the glycoprotein core, reducing its viscosity, and some of it probably increases flagelliform fiber extensibility (Sahni et al, 2011(Sahni et al, , 2014Opell et al, 2011Opell et al, , 2013Amarpuri et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Salts found in the glue droplet are hygroscopic and are hypothesized to absorb and retain atmospheric water in the glue droplet41113. Recently, Solid-State NMR investigations showed that the salts directly facilitate adhesion by solvating the glycoproteins15.…”
mentioning
confidence: 99%
“…However, both models are based on optical and physical measurements, and lack chemical evidence of heterogeneity in structure. Moreover, the recent finding that salts facilitate protein mobility at a molecular level15 suggests an alternative model where both salts and proteins are distributed ubiquitously throughout the glue droplet.…”
mentioning
confidence: 99%